Pengaruh Konsentrasi dan Lama Perendaman Giberelin terhadap Viabilitas Benih Edamame (Glycine max (L.) Merrill) Kedaluwarsa - Heln Magdalena; Putra Utama; Imas Rohmawati; Sulastri Isminingsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Edamame (Glycine max (L.) Merrill) is a soybean cultivar with high economic value, but the physiological quality of its seeds deteriorates rapidly during storage. This decline is characterized by reduced viability and vigor. To overcome this problem, priming with a gibberellin solution can be applied as a method to restore the viability of expired seeds. This research employed edamame seeds of the Biomax 2 variety that had undergone a 6 month storage period. This research aimed to determine the effects of gibberellin concentrations and soaking durations on the viability of expired edamame seeds (Glycine max (L.) Merrill). This research was conducted in Tenjo Village, Bogor Regency, West Java, from April to May 2025. The experimental design used was a factorial Randomized Complete Block Design (RCBD) with two factors: gibberellin concentration (G) and soaking duration (P). The first factor had three levels: 50 ppm, 100 ppm, and 150 ppm. The second factor had three levels: 60 minutes, 90 minutes, and 120 minutes. The observed parameters included vigor index (%), emergence time, germination rate (%), maximum growth potential (%), percentage of abnormal seedlings (%), and percentage of ungerminated seeds (%). The results showed that 100 ppm was the most effective treatment for germination rate, reaching 61.66%. A soaking duration of 90 minutes had the best effect on maximum growth potential, reaching 71.67%, while a soaking duration of 120 minutes in the highest percentage of ungerminated seeds, at 41.67%. No significant interaction was observed between gibberellin concentration and soaking duration.